2021
DOI: 10.1016/j.prosdent.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Is the therapeutic effect of occlusal stabilization appliances more than just placebo effect in the management of painful temporomandibular disorders? A network meta-analysis of randomized clinical trials

Abstract: Different treatments are available for patients with painful temporomandibular disorders (TMDs), 1 including counseling, 2 physiotherapy, 3,4 jaw exercises, 2,5 pharmacologic treatment, 6 behavioral medicine, 7,8 physical treatments, including acupuncture, 9,10 transcutaneous electrical nerve stimulation (TENS) 11 heat and cold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 72 publications
3
27
0
Order By: Relevance
“…Interestingly, Alkhytari et al have conducted a systematic review on stabilization splints in 2018 and concluded that the patient-reported treatment satisfaction, including domains other than pain relief such as psychological well-being, was beyond that of a placebo effect. The authors also suggested that, apart from the pain scale, variables concerning patient-reported satisfaction should also be considered when evaluating the efficacy of different treatment modalities [ 62 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Interestingly, Alkhytari et al have conducted a systematic review on stabilization splints in 2018 and concluded that the patient-reported treatment satisfaction, including domains other than pain relief such as psychological well-being, was beyond that of a placebo effect. The authors also suggested that, apart from the pain scale, variables concerning patient-reported satisfaction should also be considered when evaluating the efficacy of different treatment modalities [ 62 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…As highlighted earlier that there is a huge ambiguity across the literature that has reflected upon participants and may lead to failure of treatments and outcomes and reported in earlier literature. 4,16,17 A major loop hole in assessing the outcomes of occlusal appliance on management of TMDs is that the assessment is mostly subjective, which mostly relate to decrease of symptoms as reported by the patient. 10,18 Thus, there is a dire need of revisiting this important and crucial aspect of minimal intervention dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of VAS pain score and MMO was performed at the designated time points equally in both groups. Recovery was defined as a 50% reduction in VAS pain score as reported subjectively by the patients [43].…”
Section: Interventionsmentioning
confidence: 99%